Rhodanine and Thiohydantoin Derivatives for Detecting Tau Pathology in Alzheimer’s Brains - Ono, Masahiro (American Chemical Society, 2011)
[Image: see text] A novel series of rhodanin (RH) and thiohydantoin (TH) derivatives were designed and synthesized for detecting tau pathology in the brains of patients with Alzheimer’s disease (AD). In experiments in vitro using tau and β-amyloid (Aβ) aggregates, the TH derivative, TH2, showed high specific binding to tau aggregates. In hippocampal sections obtained from AD patients, TH2 intensely stained neurofibrillary tangles. In experiments using normal mice, [(125)I]TH2 showed good uptake (1.54%ID/g, 2 min postinjection) into and a rapid washout (0.25%ID/g, 60 min postinjection) from the brain. [(123)I]TH2 should be further investigated as a potential imaging agent for detecting tau pathology.